2016
DOI: 10.1134/s1023193516060069
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cobalt polyporphine and its catalytic properties in oxygen electroreduction

Abstract: International audienceA new member of the polyporphine series-cobalt polyporphine of type I (pCoP-I)-was prepared from the starting magnesium polyporphine of type I (pMgP-I) by ion exchange, i.e. by sequential processing of the pMgP-I polymer film on the electrode surface with solutions of trifluoroacetic acid (forming metalfree polyporphine of type I, pH(2)P-I) and cobalt(II) acetate in organic solvents. The completeness of each stage of ion exchange can be judged from the change in the electrochemical and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In our previous contribution in this field 34,39 we demonstrated that the magnesium(II) centers in pMgP-I could be exchanged with a cobalt(II) ion thus providing an easy, quick and repeatable way to obtain a cobalt(II) polyporphine of type I pCoP-I. Since this time we experienced that this material was unstable in aqueous matrix over potential cycling although it was designed for a use in electrochemical sensing in this medium.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous contribution in this field 34,39 we demonstrated that the magnesium(II) centers in pMgP-I could be exchanged with a cobalt(II) ion thus providing an easy, quick and repeatable way to obtain a cobalt(II) polyporphine of type I pCoP-I. Since this time we experienced that this material was unstable in aqueous matrix over potential cycling although it was designed for a use in electrochemical sensing in this medium.…”
Section: Resultsmentioning
confidence: 99%
“…1), represents a homopolymer possessing original optical and electric properties [28]. It also serves as the starting compound for synthesis of the Mg polyporphine of type II (pMgP-II) [29] as well as freebase polyporphines and polymetalloporphines of various metals [30][31][32][33][34]. These reasons have led to a detailed study of the mechanism of this polymer (pMgP-I) deposition since it is the stage which largely determines characteristics of all subsequent poly(metallo)porphines.…”
Section: Introductionmentioning
confidence: 99%